Does not hUTP14a promoter form a regulation feedback loop with P53? - Zhang, Jingyi; Guo, Yafei; Du, Xiaojuan; Xing, Baocai (Chinese Journal of Cancer Research; Vol 26, No 2 (April 26, 2014): Chinese Journal of Cancer Research, 2014)
Objective: We previously found that hUTP14a binds P53 and promotes P53 degradation. However, if hUTP14a is a downstream gene of P53 remains to be determined. This study aimed to identify the promoter of hUTP14a and investigate if hUTP14a is regulated by P53. Methods: The hUTP14a promoter region was cloned into pGL3-Basic-luciferase reporter plasmid to get pGL3-hUTP14a-luc. The reporter plasmid was transfected into 293T cells and luciferase activity was evaluated by the Dual-Luciferase Reporter Assay System. Putative transcription factors were identified through searching MatInspector Professional and Algorismica i Genetica databases. Either pGL3-hUTP14a-luc or p21 promoter reporter plasmid was co-transfected with increasing dose of p53 plasmid, and luciferase activity was evaluated. A series of deletion constructs of pGL3-hUTP14a-luc were constructed and minimal promoter region of hUTP14a was determined. Differences of the luciferase activities between different groups were assessed by statistical analysis. Results: The hUTP14a gene promoter reporter construct was correctly cloned and was demonstrated to possess promoter activity. The transcription of hUTP14a was not regulated by P53. The minimal promoter region of hUTP14a gene is located between -203 to -100 of the transcription initiation site. Conclusion: Unlike other P53-interacting proteins such as MDM2, Pirh2 and Cop I which promote P53 degradation and whose transcriptions are regulated by P53, does not hUTP14a transcription form a regulation feedback loop with P53.